Synergistic induction of the clock protein PERIOD by insulin-like peptide and prothoracicotropic hormone in Rhodnius prolixus (Hemiptera): implications for convergence of hormone signaling pathways - Vafopoulou, Xanthe; Steel, Colin G. (Frontiers in Physiology, 2014)
We showed previously that release of the cerebral neurohormones, bombyxin (an insulin-like peptide, ILP) and prothoracicotropic hormone (PTTH) from the brain have strong circadian rhythms, driven by master clock cells in the brain. These neurohormone rhythms synchronize the photosensitive brain clock with the photosensitive peripheral clock in the cells of the prothoracic glands (PGs), in which both regulate steroidogenesis. Here, using immunohistochemistry and confocal laser scanning microscopy, we show these neurohormones likely act on clock cells in the brain and PGs by regulating expression of PERIOD (PER) proteins. PER is severely reduced from the nuclei of all clock cells in continuous light, but on transfer of tissues to darkness in vitro, it is rapidly induced. A 4h pulse of either PTTH or ILPs to brain and PGs in vitro both rapidly and highly significantly induce PER in the nuclei of clock cells. Administration of both neurohormones together induces more PER than does either alone and even more than does transfer to darkness, at least in PG cells. These are clearly non-steroidogenic actions of these peptides. In the peripheral oscillators salivary gland and fat body cells, neither bombyxin nor PTTH nor darkness induced PER, but a combination of both bombyxin and PTTH induced PER. Thus PTTH and ILPs exert synergistic actions on induction of PER in both clock cells and peripheral oscillators, implying their signalling pathways converge, but in different ways in different cell types. We infer clock cells are able to integrate light cycle information with internal signals from hormones.